Human Right on Life in the Legislation of Foreign Countries - L. N. Vakhrameeva (Сибирское юридическое обозрение, 2019)
Despite the worldwide trend of recognition of human rights and freedoms, the human right to life is not constitutionally guaranteed in all national jurisdictions. This article examines the norms of the constitutional legislation of Russia and foreign countries on the human right to life. Methods of legal regulation of this right are considered by countries that recognize its constitutional value, and countries where the deprivation of human life is legally permitted, similarities and differences are revealed. The consequences of the practical application of legislative norms protecting human life are analyzed. The reasons for legal authorization of deprivation of human life are revealed. Giving the human right to life the status of an absolute right is recognized as the most effective legal way to ensure this right.